Perekonomian Pada Masa Awal Islam (Rasulullah SAW) - Frity Sintiya Silva; Ike Nurhaliza; Laysya Fadiah Azza (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article examines the economic system during the early Islamic period under the leadership of Prophet Muhammad (SAW), which marked the establishment of a revolutionary and just foundation for Islamic economic teachings. Prior to Islam, Arab society was dominated by exploitative economic practices such as usury, market monopolies, and unequal wealth distribution, resulting in significant social disparities. Through the revelations of the Qur’an and his Sunnah, Prophet Muhammad (SAW) introduced economic principles emphasizing justice, equity, and moral ethics, including the implementation of zakat as a wealth redistribution instrument, the prohibition of usury, and the enforcement of fair and transparent transactions. This study employs a descriptive qualitative approach using literature review to trace and analyze the transformation of the economic system during the Prophet’s era. The findings indicate that the Islamic economic system established by the Prophet focused not only on financial aspects but also on social and ethical dimensions, such as the prohibition of hoarding, fair price determination, and the strengthening of social solidarity through infak, charity, and waqf. This system succeeded in creating a prosperous, just, and competitive society, and serves as a model for the development of modern Islamic economics. The economic principles of Prophet Muhammad (SAW) remain relevant for building a sustainable and socially just economic order today.